Sistema de perclorato de cobre (II) - glicina em meio aquoso. II - Influência da força iônica - Melios , Cristo Bladimiros; Molina, Manuel; Jafelicci Junior, Miguel; Luchiari, Luiz Carlos (Eclética Química, 1977)
.